A comparative expression analysis of gene transcripts in brain tissue of non-transgenic and GH-transgenic zebrafish (Danio rerio) using a DDRT-PCR approach - Alves-Costa, Fernanda A. [UNESP]; Figueiredo, Márcio A.; Lanes, Carlos F.C.; Almeida, Daniela V.; Marins, Luis F.; Wasko, Adriane Pinto [UNESP] (Academia Brasileira de Ciências, 2012)
A presença de níveis mais elevados do hormônio de crescimento (GH) em animais transgênicos poderia levar a várias alterações fisiológicas. Uma linhagem transgênica de paulistinha (Danio rerio) para o GH foi comparada com amostras não transgênicas (NT) desta espécie, através de uma abordagem de DDRT-PCR, com o objetivo de identificar transcritos candidatos diferencialmente expressos em tecido cerebral que poderiam estar envolvidos na superexpressão de GH. Análises densitométricas de dois produtos de amplificação selecionados, p300 e ADCY2, apontaram uma expressão gênica significativamente menor nas amostras transgênicas de paulistinha (104.02 ± 57.71; 224.10 ± 91.73), quando comparadas com as amostras NT (249.75 ± 30.08; 342.95±65.19). Os presentes dados indicam que p300 e ADCY2 estão envolvidos em um sistema de regulação do GH, quando altos níveis circulantes desse hormônio são encontrados em paulistinha.

The presence of higher level of exogenous growth hormone (GH) in transgenic animals could lead to several physiological alterations. A GH transgenic zebrafish (Danio rerio) line was compared to nontransgenic (NT) samples of the species through a DDRT-PCR approach, with the goal of identifying candidate differentially expressed transcripts in brain tissues that could be involved in GH overexpression. Densitometric analyses of two selected amplification products, p300 and ADCY2, pointed to a significant lower gene expression in the transgenic zebrafish (104.02 ± 57.71; 224.10 ± 91.73) when compared to NT samples (249.75 ± 30.08; 342.95 ± 65.19). The present data indicate that p300 and ADCY2 are involved in a regulation system for GH when high circulating levels of this hormone are found in zebrafishes.
Keywords: Display diferencial; GH; hormônio de crescimento; transgênico; paulistinha; Differential display; GH; growth hormone; transgenic; zebrafish